Determinants of immigrants' cash-welfare benefits intake in Spain - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2012)
Much of the literature on immigrants' cash-welfare benefits use has focused on countries with a large tradition of receiving immigrants and with well established Welfare states. This paper contributes to this literature by analyzing differences in cash-welfare benefits receipt between immigrants and natives and their determinants in Spain, a country with: (1) a small level of social assistance and a Welfare state heavily reliable on conditioned access to pensions; and (2) an unprecedented immigration boom. Different probit models of social program intake are estimated for immigrants and native-born individuals using pooled cross-sectional data from the 1999 to 2009 Spanish Labor Force Survey. Results show that a negative residual welfare gap exists and that it is mainly driven by recently arrived immigrants, whose legal status or insufficient contribution is likely to hamper participation in social programs. In addition, I find that immigrants with more than 5 years in the host country are more likely to receive unemployment benefits than natives, consistent with findings in other countries. These findings hold regardless of immigrants' continent of origin.
urn:nbn:de:101:1-201301188917
Keywords: J15; J61; J68; I38; 330; Southern European welfare state; immigrants' residual welfare use; Migranten; Sozialhilfeempfänger; Arbeitslosenversicherung; Spanien